Genetic Relationship Among the Kazakh People Based on Y-STR Markers Reveals Evidence of Genetic Variation Among Tribes and Zhuz - Khussainova, Elmira; Kisselev, Ilya; Iksan, Olzhas; Bekmanov, Bakhytzhan; Skvortsova, Liliya; Garshin, Alexander; Kuzovleva, Elena; Zhaniyazov, Zhassulan; Zhunussova, Gulnur; Musralina, Lyazzat; Kahbatkyzy, Nurzhibek; Amirgaliyeva, Almira; et al. (Frontiers in Genetics, 2022)
Ethnogenesis of Kazakhs took place in Central Asia, a region of high genetic and cultural diversity. Even though archaeological and historical studies have shed some light on the formation of modern Kazakhs, the process of establishment of hierarchical socioeconomic structure in the Steppe remains contentious. In this study, we analyzed haplotype variation at 15 Y-chromosomal short-tandem-repeats obtained from 1171 individuals from 24 tribes representing the three socio-territorial subdivisions (Senior, Middle and Junior zhuz) in Kazakhstan to comprehensively characterize the patrilineal genetic architecture of the Kazakh Steppe. In total, 577 distinct haplotypes were identified belonging to one of 20 haplogroups; 16 predominant haplogroups were confirmed by SNP-genotyping. The haplogroup distribution was skewed towards C2-M217, present in all tribes at a global frequency of 51.9%. Despite signatures of spatial differences in haplotype frequencies, a Mantel test failed to detect a statistically significant correlation between genetic and geographic distance between individuals. An analysis of molecular variance found that ~ 8.9% of the genetic variance among individuals was attributable to differences among zhuzes and ~ 20% to differences among tribes within zhuzes. The STRUCTURE analysis of the 1164 individuals indicated the presence of 20 ancestral groups and a complex three-subclade organization of the C2-M217 haplogroup in Kazakhs, a result supported by the multidimensional scaling analysis. Additionally, while the majority of the haplotypes and tribes overlapped, a distinct cluster of the O2 haplogroup, mostly of the Naiman tribe, was observed. Thus, firstly, our analysis indicated that the majority of Kazakh tribes share deep heterogeneous patrilineal ancestries, while a smaller fraction of them are descendants of a founder paternal ancestor. Secondly, we observed a high frequency of the C2-M217 haplogroups along the southern border of Kazakhstan, broadly corresponding to both the path of the Mongolian invasion and the ancient Silk Road. Interestingly, we detected three subclades of the C2-M217 haplogroup that broadly exhibits zhuz-specific clustering. Further study of Kazakh haplotypes variation within a Central Asian context is required to untwist this complex process of ethnogenesis